PENGARUH PERSEPSI KORUPSI PAJAK, MOTIVASI PAJAK, DAN INSENTIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KABUPATEN BANTUL, PROVINSI DIY - Muhammad Arifudin; Diana Airawaty (ITB AAS Indonesia Surakarta, 2026)
This study was conducted to determine the influence of perceptions of tax corruption, tax motivation, and tax incentives on taxpayer compliance among MSMEs in Bantul Regency, Yogyakarta Special Region (DIY). The population in this study was all MSMEs, both individuals and corporations, that already have a Taxpayer Identification Number (NPWP) in Bantul Regency. Data analysis used SPSS. The SPSS output shows that perceptions of tax corruption have a positive and significant effect on MSME taxpayer compliance. Tax motivation has a positive and significant effect on MSME taxpayer compliance. Tax incentives have a positive and significant effect on MSME taxpayer compliance. The provision of tax incentives can increase taxpayer awareness and compliance, especially among MSMEs. The results indicate that the hypothesis is accepted.